2021
DOI: 10.1038/s41598-021-92355-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between Meniere’s disease and air pollution in South Korea

Abstract: Meniere’s disease is thought to be a disorder of the inner ear function, affected by genetic and environmental factors. Several recent studies have shown that air pollution could affect middle and inner ear diseases. The purpose of this study was to investigate the relationship between the Meniere’s disease occurrence and air pollution status in Korea. This study used a time-stratified case-crossover design. Hospital visit data by Meniere’s disease were collected from the Korea National Health Insurance Servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 85 publications
0
8
0
1
Order By: Relevance
“…The study outcome was the development for Meniere’s disease based on two or more claims of the diagnostic code H810 with a previous audiometric examination (claim code: E6931–E6937, F6341–F6348) [ 17 , 18 ]. The participants were followed up one day after the date of the oral health examination until the occurrence of Meniere’s disease, death or December 2020, whichever came first.…”
Section: Methodsmentioning
confidence: 99%
“…The study outcome was the development for Meniere’s disease based on two or more claims of the diagnostic code H810 with a previous audiometric examination (claim code: E6931–E6937, F6341–F6348) [ 17 , 18 ]. The participants were followed up one day after the date of the oral health examination until the occurrence of Meniere’s disease, death or December 2020, whichever came first.…”
Section: Methodsmentioning
confidence: 99%
“…Significantly lower serum vitamin D level was noted in another study [16]. Air pollution was also shown to be associated with higher hospital visits for Meniere's disease [17]. One Iranian study measured the immunoreactivity to food allergens and found that Meniere's disease patients are more reactive than control group [18].…”
Section: Key Pointsmentioning
confidence: 96%
“…Распространенность БМ в США варьирует от 9 на 100 000 населения у пациентов в возрасте до 18 лет и до 440 на 100 000 населения у пациентов в возрасте ≥65 лет [10]. Представлена распространенность БМ в США по гендерному признаку, свидетельствующая о том, что в настоящее время данное заболевание преобладает среди женского населения (в 1,3-1,51 раза) [11].…”
Section: эпидемиологияunclassified